2015
DOI: 10.1370/afm.1747
|View full text |Cite
|
Sign up to set email alerts
|

Is a Strategy Focused on Super-Utilizers Equal to the Task of Health Care System Transformation? No.

Abstract: To read or post commentaries in response to this article, see it online at http://www.annfammed.org/content/13/1/8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This is dramatically different than other studies that have investigated super users. [ 27 , 42 44 ] One explanation for the differences between emergency department utilization rates between our study and previous studies is that we used the top 25 percent as the cut point for high healthcare utilization. If we had used the top five or one percent AHRQ values, we would have likely obtained more information about super utilizers versus high utilizers of healthcare.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This is dramatically different than other studies that have investigated super users. [ 27 , 42 44 ] One explanation for the differences between emergency department utilization rates between our study and previous studies is that we used the top 25 percent as the cut point for high healthcare utilization. If we had used the top five or one percent AHRQ values, we would have likely obtained more information about super utilizers versus high utilizers of healthcare.…”
Section: Discussionmentioning
confidence: 84%
“…More importantly was the way we defined high healthcare utilization. It has been termed healthcare super utilization;[ 27 ] however, this term has not been consistently defined across studies. Depending on the study, super utilization rates range from the top one to top ten percent (or more) of healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, the target population might experience future utilization rates that differ from those observed before the year of the intervention. Prior research has observed the regression‐to‐the‐mean phenomenon, in which many of the highest users of health care in a population in a given year typically do not have a similar high rate of use the following year . To investigate the impact of the assumption of unchanged utilization rates over time, we conducted sensitivity analysis by varying the annual number of hospitalizations that would occur without the intervention in Group 3 from 100% of the hospitalizations observed in the year before the intervention (likely an overestimation of the intervention effect) down to 5% of that hospitalization rate.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with very high levels of hospitalizations and emergency room visits, sometimes identified as “super-utilizers,” 1 often represent a population with unmet healthcare needs. Though patients in this group are heterogeneous and difficult to define across settings, 2 they frequently have poor access to care, complex medical and social problems, and high healthcare costs. Programmatic interventions that target this group share the goal of improving care quality, and often employ care management to address the myriad psychosocial factors that complicate care, such as poor housing conditions, poverty, substance abuse, and mental illness.…”
Section: Casementioning
confidence: 99%